Die Prüfung Abrahams (Genesis 22) und ihre innerbiblischen Bezüge - Levin, Christoph (Zeitschrift für Theologie und Kirche, 2021)
The testing of Abraham in Gen. 22:1-19 is a parable created from many inner-biblical references. Its core is based on Gen. 12:1-7 and Exod. 3:1-5, and in further adaptations the event was moved to the mountain of God, following the example of Exod. 24:1-2, 13-14. The preparations for the sacrifice were added according to the Torah for the burnt offering in Lev 1:1-9. As in Gen. 28:19; 16:13; 32:31, special significance was ascribed to the site. In the second speech of the angel, the promises made to the fathers were given a collective messianic interpretation using Jer. 22:3-5. Lastly, the expulsion of Ishmael (Gen. 21:9-21) was taken into account, which is told along the lines of Gen 22. The passage Gen. 22 had a broad inner-biblical impact itself. Its traces can be seen in Gen. 21:9-21; 26:3-5, 24; Exod. 20:19-20; 24:11; 2Sam. 12:6; Job 1-2, among others.